METHODOLOGY FOR CALCULATING THE BEARING CAPACITY OF THE PLATE AND THE MAIN BEAMS OF THE INTERMEDIATE DEVICE OF BUILDINGS AND STRUCTURES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article presents the method and scheme for calculating the load-carrying capacity of the intermediate device plate and the main beam of buildings and structures.